Subsphaerolaimus minor sp. n. and Micromicron cephalatum Cobb, 1920 (Nematoda) from the Yen River Estuary of Vietnam - Gagarin, Vladimir G.; Thanh, Nguyen Vu (Zootaxa, 2015)
Two nematode species found in Yen River Estuary of Vietnam are described and illustrated. Subsphaerolaimus minor sp. n. is similar to S. lamasus Gerlach, 1956, but differs from it in the shorter body, comparatively shorter pharynx and shorter cephalic setae. A pictorial key for determination of valid species in the genus Subsphaerolaimus Lorenzen, 1978 is given. Micromicron cephalatum Cobb, 1920 is redescribed and reillustrated based on numerous males and females. The genus Micromicron Cobb, 1920 is confirmed as a valid genus with type and only species, M. cephalatum Cobb, 1920.